Advances of Targeted Therapy for Hepatocellular Carcinoma - Niu, Mengke; Yi, Ming; Li, Ning; Wu, Kongju; Wu, Kongming (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is one of the common and fatal malignancies, which is a significant global health problem. The clinical applicability of traditional surgery and other locoregional therapies is limited, and these therapeutic strategies are not satisfactory in improving the outcomes of advanced HCC. In the past decade, targeted therapy had made a ground-breaking progress in advanced HCC. Targeted therapy exerts antitumor effects through anti-angiogenesis or cell cycle arrest. As a standard systemic therapy option, it tremendously improves the survival of this devastating disease. Moreover, the combination of targeted therapy with immune checkpoint inhibitor (ICI) has demonstrated more potent anticancer effects and becomes the hot topic in clinical studies. The combining medications bring about a paradigm shift in the treatment of advanced HCC. In this review, we presented all approved targeted agents for advanced HCC with an emphasis on their clinical efficacy, summarized the advances of multi-target drugs in research for HCC and potential therapeutic targets for drug development. We also discussed the exciting results of the combination between targeted therapy and ICI.